2018
DOI: 10.3747/pdi.2017.00196
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Cuff Migrates after Initiation of Peritoneal Dialysis

Abstract: The aim of this study was to determine whether subcutaneous cuffs migrate toward the exit site after initiation of peritoneal dialysis (PD) and to clarify the factors affecting such migration. Subcutaneous cuff migration was defined as extension of the length of the external catheter. In this single-center, retrospective study, the external catheter lengths at initiation and 1 year later were compared in 33 PD patients (median age 62 years; 64% men; 49% with diabetes mellitus). The correlations between patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The term cuff extrusion (CE) encompasses all cases where the Dacron cuff is visible outside the tunnel, either completely or partially, and includes those cases where the entire catheter is outside the body (catheter fall-out). This noninfectious complication is well documented for peritoneal dialysis catheters 2,3 and its incidence has been reported for hemodialysis catheters in pediatric populations with incidence of up to 25% 4 and a rate of 2.4 episodes/1,000 catheter-days. 5 For adult patients, although it has been previously mentioned in the literature, [6][7][8][9] it has never been the focus of attention and some publications do not discuss it as a possible complication.…”
Section: Introductionmentioning
confidence: 96%
“…The term cuff extrusion (CE) encompasses all cases where the Dacron cuff is visible outside the tunnel, either completely or partially, and includes those cases where the entire catheter is outside the body (catheter fall-out). This noninfectious complication is well documented for peritoneal dialysis catheters 2,3 and its incidence has been reported for hemodialysis catheters in pediatric populations with incidence of up to 25% 4 and a rate of 2.4 episodes/1,000 catheter-days. 5 For adult patients, although it has been previously mentioned in the literature, [6][7][8][9] it has never been the focus of attention and some publications do not discuss it as a possible complication.…”
Section: Introductionmentioning
confidence: 96%
“…Cuff extrusion has also been reported in peritoneal dialysis catheters [3,4]. In a recent study of the adult population, it was observed that the risk of cuff extrusion in dialysis patients increased with obesity, a history of previous cuff extrusion, certain catheter models, and the absence of wing sutures.…”
Section: Introductionmentioning
confidence: 98%